Pseudolaguvia ferula, a new species of sisoroid catfish (Teleostei: Erethistidae) from India - Ng, Heok Hee (Zootaxa, 2006)
Pseudolaguvia ferula, a new species of erethistid catish, is described from the Brahmaputra River drainage in India. It can be distinguished from congeners in having a terete (vs. depressed) head and body, manifested in the narrower head width (17.1–19.1% SL vs. 19.4–23.4), a smaller anterior fontanel (about one third the length of the frontals vs. at least half the length), and very faint, poorly contrasting cream bands that are sometimes absent on some individuals (vs. sharply contrasting cream bands on a brown body). It can be further distinguished from congeners in having a unique combination of the following characters: dorsal-spine length 17.3–18.7% SL, pectoral-spine length 20.2–24.3% SL, pelvic-fin length 13.0–14.7% SL, length of adipose-fin base 11.5–13.0% SL, caudal peduncle depth 6.9–7.8% SL, body depth at anus 12.1–13.8% SL, eye diameter 8.6–11.7% HL, vertebrae 28–30, and thoracic adhesive apparatus reaching to midway between bases of last pectoral-fin ray and first pelvic-fin ray. with its unculiferous ridges joined at their posterior ends.